Multicomponent solid forms of antibiotic cephalexin towards improved chemical stability. Issue 8 (31st January 2023) - Fayaz, T. K. S.; Palanisamy, Vasanthi; Sanphui, Palash; Chernyshev, Vladimir
Abstract : Chemical stability of antibiotic cephalexin was improved by 2-fold in acidic medium using crystal engineering approach. Abstract : Cephalexin (CPX) is a first-generation β-lactam antibiotic with great efficiency to kill Gram-positive and Gram-negative bacteria. Although the drug belongs to the BCS class I category of high solubility/permeability, it exhibits up to 20% degradation in acidic medium (pH 1.2). In order to improve its chemical stability, pharmaceutical cocrystal screening was carried out with a variety of ionizable/zwitterionic carboxylic acids and amino acids that resulted in a cocrystal with serine (SER), a cocrystal hydrate with 4-hydroxybenzoic acid (PHB) and a salt hydrate with 2, 6-dihydroxybenzoic acid (DHB). A liquid-assisted grinding method was employed to obtain the multicomponent solid forms of CPX. The novel solid forms were characterized by powder X-ray diffraction (PXRD), FT-IR spectroscopy and thermal methods (DSC, TGA). The crystal structures of CPX–SER and CPX–DHB were solved in chiral space groups ( P 21 21 21 / P 21 ) by powder XRD and single-crystal XRD techniques. Multiple functional groups in flexible CPX along with the coformer resulted in a complex hydrogen bonding network. The CPX–coformer heterosynthon is the key to forming multicomponent solids, although ionic interactions between the quaternary ammonium cation and the carboxylate ion of CPX are robust in all the solid forms. All the multicomponent solid forms were stable under 35 ± 5 °C and 75 ± 5% relative humidity conditions for a month. An aqueous stability experiment in 0.1 N HCl medium showed that the chemical stability of the novel multicomponent solids of CPX improved up to 2-fold compared to the commercial CPX monohydrate.